Improving Scan Compliance while Decreasing Medication Errors - Christianna Conn (My University, 2025)
Previous studies examining scan compliance have revealed that many nurses do not follow proper protocols when scanning medications for their patients. In response to low scan compliance rates throughout the unit, on-site education, bedside audits, and informational handouts were provided to nurses working in a community hospital. This quality improvement project highlighted that enhanced education and staff engagement can significantly boost scan compliance rates and increase staff awareness of medication errors and near misses.
Improving Scan Compliance while Decreasing Medication Errors in the Hospital
Keywords: Scan compliance; BCMA; Medication errors; Near Miss; Work arounds